Evaluation of the anti-Schistosoma mansoni activity of thiosemicarbazones and thiazoles - Santiago, Edna de Farias (2014)
Conselho Nacional de Desenvolvimento Científico e Tecnológico (CPNq) and Fundação Oswaldo Cruz (FIOCRUZ). FAPESB postdoctoral scholarship.